2013
DOI: 10.1111/1556-4029.12188
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Estimating Sex Using the Clavicle, Humerus, Radius, and Ulna

Abstract: Sex estimation from skeletal remains can be an important part of preliminary identification. The best source of information for estimating sex is the pelvis but it is not always available for analysis. For these cases, a probabilistic sex estimation method is presented using combinations of standard and alternative measurements of the clavicle, humerus, radius, and ulna. Various equations are developed that are not population specific and that are applicable in various recovery scenarios. The equations were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 19 publications
(26 reference statements)
0
32
0
9
Order By: Relevance
“…The proposed method for sex estimation is comparable to other metric methods that have an accuracy range of 87.4–98.5% in which all utilize a diverse range of body parts such as pelvis and hip , femur , humerus , and other postcranial elements . These rates of accuracy are higher than more visual, morphometric methods which had a range of high 70% and low 80% .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The proposed method for sex estimation is comparable to other metric methods that have an accuracy range of 87.4–98.5% in which all utilize a diverse range of body parts such as pelvis and hip , femur , humerus , and other postcranial elements . These rates of accuracy are higher than more visual, morphometric methods which had a range of high 70% and low 80% .…”
Section: Discussionmentioning
confidence: 83%
“…However, when the pelvis is not present, the skull is often considered the next most reliable bone (6). Other studies have suggested postcranial bones may be more effective (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) in estimating sex. In general, once the sex of an unknown individual is estimated, one of the next steps is the approximation of their age.…”
mentioning
confidence: 99%
“…Therefore, if the skeleton is reasonably complete and a reliable morphological diagnosis is possible, there is no need to apply molecular methods. In such cases, sex estimation can generally be detected by two different approaches: observation of morphological trials and/ or measurement of different bones (Asala et al 2004;Cowal and Pastor 2008;Robinson and Bidmos 2011;Spradley and Jantz 2011;Albanese 2013;Bašić et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Morphological and metric analysis for sex assessment have been used extensively on different skeletal elements [4][5][6][7][8] with the assumption that the metrical approach relies on a statistical foundation; the underlying quantitative analysis based on statistical principles has proven to be a reliable substitute for the more subjective traditional gross-examination [9]. However, as the degree of sexual dimorphism is not constant across populations, population specific metric standards are highly recommended [7,10,11].…”
Section: Introductionmentioning
confidence: 99%